Simple Reversed-Phase HPLC Method with Spectrophotometric Detection for Measuring Acetaminophen-Protein Adducts in Rat Liver Samples - Miteshkumar Acharya; Cesar A. Lau-Cam (The Scientific World Journal)
A simple reversed-phase HPLC method for measuring hepatic levels of acetaminophen- (APAP-) protein adduct following an overdose of APAP was developed. An aliquot of liver homogenate in phosphate-buffered saline pH 7.4 (PBS) was placed on a Nanosep centrifugal device, which was centrifuged to obtain a protein residue. This residue was incubated with a solution of p-aminobenzoic acid (PABA), the internal standard, and bacterial protease in PBS, transferred to a Nanosep centrifugal device, and centrifuged. A 100 μL portion of the filtrate was analyzed on a YMC-Pack ODS-AMQ C18 column, using 100 mM potassium dihydrogen phosphate-methanol-acetic acid (100 : 0.6 : 0.1) as the mobile phase, a flow rate of 1 mL/min, and photometric detection at 254 nm. PABA and APAP-cystein-S-yl (APAP-Cys) eluted at ~14.7 min and 22.7 min, respectively. Method linearity, based on on-column concentrations of APAP-Cys, was observed over the range 0.078–40 μg. Recoveries of APAP-Cys from spiked blank liver homogenates ranged from ~83% to 91%. Limits of detection and of quantification of APAP-Cys, based on column concentrations, were 0.06 μg and 0.14 μg, respectively. RSD values for interday and intraday analyses of a blank liver homogenate spiked with APAP-Cyst at three levels were, in all cases, ≤1.0% and <1.5%, respectively. The proposed method was found appropriate for comparing the antidotal properties of N-acetylcysteine and taurine in a rat model of APAP poisoning.